Total gut balance : fix your mycobiome fast for complete digestive wellness - Ghannoum, Mahmoud A. (Mahmoud Afif); Adamson, Eve (The Countryman Press, 2019)
Most people understand the importance of a healthy gut microbiome for digestive health and overall wellbeing. But what about the mycobiome--the fungi that live inside our bodies? Here, Dr. Mahmoud Ghannoum introduces this important component of the microbiome and explains how diet affects this population and how its balance or imbalance can cause you to feel--a poor balance of fungi can lead to weight gain, pain and bloating, and low energy, and can worsen symptoms for those with IBS or Crohn's. Good news: Gut fungi respond quickly and dramatically to dietary and lifestyle changes. Within 24 hours, you can remake your mycobiome, supporting a path to weight loss, better digestion, and more energy. Alongside this accessible gut science, Ghannoum outlines fast changes for fostering healthy fungi as well as 7- and 20-day diet plans, with more than 50 dietician-tested recipes, to cultivate a thriving mycobiome and methods for tweaking your lifestyle for long-term gut health.